Influence of the exacerbation of patellofemoral pain on trunk kinematics and lower limb mechanics during stair negotiation - Briani, Ronaldo Valdir [UNESP]; Cannon, Jordan; Waiteman, Marina Cabral [UNESP]; Negrão Filho, Rúben de Faria [UNESP]; Magalhães, Fernando Henrique [UNESP]; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2021)
Background: Although it is assumed that the presence of patellofemoral pain (PFP) may result in compensatory behaviors that can alter trunk kinematics and lower limb mechanics, the influence of the exacerbation of patellofemoral pain on trunk kinematics and lower limb mechanics during stair negotiation has not been established. Research question: Does the exacerbation of PFP symptoms lead to altered trunk kinematics and lower limb mechanics during stair negotiation? Methods: Three-dimensional kinematics and kinetics were obtained from 45 women with PFP during stair descent and ascent. Data were obtained before and after a pain exacerbation protocol. The variables of interest were peak trunk, hip, and knee flexion, and ankle dorsiflexion; peak hip, and knee extensor, and ankle plantarflexor moments. Paired t-tests were used to compare the variables of interest before and after pain exacerbation. Results: Following pain exacerbation, there was a decrease in peak knee extensor moment during stair descent (Effect size = −0.68; p = 0.01) and stair ascent (Effect size = −0.56; p = 0.02); as well as in peak ankle dorsiflexion during stair descent (Effect size = −0.33; p = 0.01) and stair ascent (Effect size = −0.30; p = 0.01). An increase in ankle plantarflexor moment during stair descent (Effect size = 0.79; p < 0.01) and stair ascent (Effect size = 0.89; p < 0.01) was also observed. No significant differences were observed for peak trunk, hip, and knee flexion or hip extensor moment (p > 0.05). Significance: Our findings show compensatory strategies used by people with PFP in response to symptoms exacerbation that may have a negative impact on knee and ankle mechanics. Our findings also suggest that people with PFP do not seem to change their trunk, hip, and knee flexion or hip extensor moment during stair negotiation in response to symptom exacerbation.
Keywords: Anterior knee pain; Joint moments; Osteoarthritis; Patellofemoral joint; Tibiofemoral joint